2003
DOI: 10.1007/s00592-003-0093-z
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in abdominal visceral fat accumulation between Japanese, African-Americans, and Caucasians: a meta-analysis

Abstract: A meta-analysis was performed in order to test the hypothesis that Japanese have a greater amount of abdominal visceral fat (AVF) relative to abdominal subcutaneous fat (ASF) than Caucasians. Data were derived from published studies that included mean values for AVF and ASF areas, measured using computed tomography, and age for native Japanese, African-Americans, and Caucasians of both genders. Mean values from each study were used as single data points. A significant difference in AVF was observed between Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
99
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 5 publications
2
99
0
1
Order By: Relevance
“…There have been reports of racial differences in abdominal fat distribution between Caucasians and Africans, 6 Hispanics, 7 and Asians. 8,9 Previous studies have shown that Asian-American and Caucasian men had no significant difference in VAT among volunteer participants. 8 Likewise, a meta-analysis showed no significant difference in VAT between Japanese and Caucasian men.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been reports of racial differences in abdominal fat distribution between Caucasians and Africans, 6 Hispanics, 7 and Asians. 8,9 Previous studies have shown that Asian-American and Caucasian men had no significant difference in VAT among volunteer participants. 8 Likewise, a meta-analysis showed no significant difference in VAT between Japanese and Caucasian men.…”
mentioning
confidence: 99%
“…8 Likewise, a meta-analysis showed no significant difference in VAT between Japanese and Caucasian men. 9 In these studies, VAT was compared after adjusting for other factors such as age and obesity. There has been no report directly comparing VAT between the Japanese and Caucasian men in a population-based sample.…”
mentioning
confidence: 99%
“…Indeed, Park et al reported that Asians living in the US have a comparable amount of visceral fat to that of European Americans [59]. Moreover, a meta-analysis showed that visceral fat in Japanese population was significantly lower than that in Caucasians [60]. Obviously, visceral fat may modify drug distribution and thus decrease drug exposure in the tumor [61].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Asians have a greater tendency than Caucasians to deposit adipose tissue as abdominal visceral fat rather than abdominal subcutaneous fat. 5,6 Probably due to increased intraabdominal fat deposition, Japanese are susceptible to T2DM and cardiovascular disease despite a relatively normal body mass index (BMI). 5,6 Taking this into account, the International Diabetes Institute (IDI), a center that collaborates with the World Health Organization (WHO), proposed specifi c values to characterize total and abdominal obesity in Asian populations.…”
mentioning
confidence: 99%
“…5,6 Probably due to increased intraabdominal fat deposition, Japanese are susceptible to T2DM and cardiovascular disease despite a relatively normal body mass index (BMI). 5,6 Taking this into account, the International Diabetes Institute (IDI), a center that collaborates with the World Health Organization (WHO), proposed specifi c values to characterize total and abdominal obesity in Asian populations. Subjects with BMI values between 25.0 and 29.9 kg/m 2 and BMI ≥30.0 kg/m 2 were classifi ed as I and II degree obesity, respectively, and associated with moderate and severe risk for developing co-morbidities.…”
mentioning
confidence: 99%